Exposure of Skin Homografts from Related Living Donors to Radiotherapy and Its Effects on Acute Rejection and Wound Healing in Children with Deep Burns: A Randomized Controlled Trial - Megahed, Mohammed Ahmed; Kashty, Sherief Mohamed El; Nassar, Ahmed Tharwat; Aboulfetouh, Mohamed; AboShaban, Mohammed Saad (Indian Journal of Plastic Surgery, 2022)
Background The ideal skin substitute should be more similar to normal skin function while causing fewer reactions. The purpose of this study was to assess the effect of radiotherapy on minimizing acute rejection and enhancing wound healing in children with deep burns.Patients and Methods A prospective randomized control study included 34 children admitted to the burn unit with deep burns under the age of 12 years. Through the tomotherapy device, a skin homograft from a related living donor was exposed to a local dose of radiotherapy of 500 centigray (cGy). It was immediately used for coverage of the prepared bed after the irradiation was completed.Results The mean values of the laboratory parameters (ESR, CRP, IL-6, and TNF) for all burn patients in the study showed a significant difference, with p < 0.001. The mean ± standard deviation (SD) of the time from homograft coverage to the appearance of rejection was 9.62 ± 1.45 in group 1 and 14.35 ± 2.8 in group 2, with p < 0.001 (highly significant difference), indicating that exposure to radiotherapy can reduce graft rejection.Conclusions The exposure of skin homografts from related living donors to a local low dose of radiotherapy can reduce a graft's ability to initiate inflammatory and immunological reactions, thereby minimizing rejection of a graft and enhancing epithelialization in children with deep second- and third-degree burns.
Keywords: burn; deep; children; homograft; radiotherapy; rejection